Dynamic single/dual channel filter with smart temperature set based on electromagnetic tunable FBG - ZHANG Duo-ying1; LIU Min1; LI Jian-dong2 (Tongxin xuebao)
A cascaded fiber Bragg gratings filter module was proposed,which can act either as a tunable single channel filter with its central wavelength and/or bandwidth being tunable,or as a double channel filter with its central wavelength being tunable.The filter is applied strain by electromagnetic force.The temperature of magnet is controlled by semicon-ductor equipment.The test results show that the filter can realize the optical channel is added/dropped in the MAN optical network simply and flexible.